A Selection of Modern English Prose - Complied and Edited by Sajjad Shaikh Prof. (Lahore Poymer Publications, 1981)
"To gain a full understanding of the literature and history of early modern England, students need to study the prose of the period. Aiming to make early modern prose more visible to teachers, this volume approaches prose as a genre that requires as much analysis and attention as the drama and poetry of the time. The essays collected here consider the broad cultural questions raised by prose and explore prose style
Keywords: English prose literature -- Early modern, 1500-1700 -- Study and teaching